Is the Internet Sufficient and Trustworthy for Torticollis Parents? Evaluation of Online Information for Torticollis - Yalin, Mustafa; Key, Sefa (Galenos Publ House, 2024)
Objective: The purpose of this study was to assess the readability and quality of torticollis-related web content. Methods: The top 3 browsers were determined. The 2 reviewers structured their websites according to type. Each one's quality was determined based on whether or not it conformed to the Health On the Net (HON) code as well as using some scoring tools such as the DISCERN score, Journal of American Medical Association (JAMA) benchmark, and Global Quality score (GQS). To evaluate readability, the Flesch-Kincaid grade Results: Sixty websites were identified. The categories were as follows: 12 (20%) academic, 26 (43.3%) medical, 13 (21.7%) physician, and 9 (15%) commercial. The DISCERN, JAMA, GQS, FKGL, and Torticollis-Specific Content (TSC) scores of the academic category were significantly higher than those of the other categories. Websites with a HON code had considerably higher DISCERN, JAMA, GQS, and TSC scores than those without it (p<0.05). Conclusion: Most material on the websites reviewed in this study was of low quality. Despite the higher quality of academic resources, the material was challenging to comprehend. The current study can aid in the evaluation of information that may be important for preserving equilibrium in patient-doctor relationships.
Tortikollis Ebeveynleri için İnternet Yeterli ve Güvenilir mi? Tortikollis için Çevrimiçi Bilgilerin Değerlendirilmesi
Keywords: Torticollis; internet; search engine; information